Protection of Autonomous Microgrids Using Agent-Based Distributed Communication - Cintuglu, Mehmet H.; Tan Ma; Mohammed, Osama A. (IEEE transactions on power delivery, 2017)
This paper presents a real-time implementation of autonomous microgrid protection using agent-based distributed communication. Protection of an autonomous microgrid requires special considerations compared to large-scale distribution networks due to the presence of power converters and relatively low inertia. In this paper, we introduce a practical overcurrent and a frequency-selectivity method to overcome conventional limitations. The proposed overcurrent scheme defines a selectivity mechanism considering the remedial action scheme of the microgrid after a fault instant based on feeder characteristics and the location of the intelligent electronic devices (IEDs). A synchrophasor-based online frequency-selectivity approach is proposed to avoid pulse loading effects in low inertia microgrids. Experimental results are presented for verification of the proposed schemes using a laboratory-based microgrid. The setup was composed of actual generation units and IEDs using the IEC 61850 protocol. The experimental results were in excellent agreement with the proposed protection scheme.